The effects of Moringa Oleifera extract on the seminiferous epithelium in pre-mature male rats. - Saenphet, K.; Khrongkaew, C.; Saenphet, S.; U-pathi, J.; Sudwan, P. (Chulalongkorn Medical Journal, 2023)
Background : Moringa oleifera (M. oleifera) Lam. is an herb, widely regarded for its nutritional and medicinal properties. It is promoted as a dietary supplement to prevent and treat malnutrition. M. oleifera leaves also contain many antioxidants. Objective : This study was aimed to assess the safety of the extract from M. oleifera leaves on gametogenesis in pre-mature male rats. Methods : Forty pre-mature male Wistar rats, 4-5 week-old, were divided into five groups. They were administered orally with aqueous extracts of M. oleifera at the doses of 60, 120, 180 and 240 mg/kg BW for 60 consecutive days, while the control-group received only distilled water (1 ml/day). At day 61, the testes of all rats were weighed and processed for histological investigation. Results : The results showed that the control group and the group that was given 60 mg/kg BW of M. oleifera leaves extract contained most seminiferous epithelium development during stage I, while the doses of 180 and 240 mg/kg BW had a more developed seminiferous epithelium during the stage XII. Moreover, at the dose of 120 mg/kg BW the most development of seminiferous epithelium was at stages I and XII equally. Finally, testicular weight and seminiferous tubule diameter of all experimental groups receiving the extract of M. oleifera were not significantly different from those in the control group. Conclusion : The findings of this study indicated that the aqueous extract from M. oleifera leaves are safe for seminiferous epithelium and the reproductive organs of the male rats. It may also be beneficial for reproduction by stimulating the development of the male reproductive tract.